(untitled) (Journal of Small Business Strategy (archive only), 2015)
We examine how entrepreneurial ventures can employ sustainability to do well (create a competitive advantage) by doing better (creating more social good than is created by Corporate Social Responsibility). We compare and constrast CSR and sustainability and examine factors influencing the competitive strategies of large, established firms versus entrepreneurial firms. We conclude that established firms are likely to focus on CSR while entrepreneurial ventures are more likely to pursue sustainability as a strategy for creating private and social value and durable competitive advantage. Established firms will do well by doing good, while entrepreneurial ventures will do well by doing better.